What can calculations employing empirical potentials teach us about bare transition-metal clusters? - Wales, D; Munro, L; Doye, J (1996)
The implications for transition-metal clusters of theoretical results for systems containing 10-148 atoms bound by empirical potentials have been considered. The effects of the range of the interatomic pair potential and anisotropy on the potential-energy surface are now quite well understood. For example, as the range decreases the favoured morphology changes from icosahedral to decahedral and then to cuboctahedral. Since strain increases with size the crossover between electronic and geometrical 'magic numbers' exhibited by alkali-metal clusters can be rationalised. Calculations employing specific potentials designed to represent face-centred-cubic transition metals enable the study of changes in morphology and surface migrations in clusters of these elements. Single-step mechanisms exist for highly co-operative rearrangements between different structures, but the associated barriers scale as the total number of atoms. Hence, at larger size the same mechanisms are mediated by a series of transition states. The barriers for surface processes are comparable to those deduced experimentally and theoretically for bulk surfaces. It is predicted that icosahedral order is 'frozen in' at relatively small size and Mackay icosahedra grow via anti-Mackay and then Mackay overlayers.